PSYCHOLOGICAL FEATURES OF THE DEVELOPMENT OF EMOTIONAL-ETHICAL COMPETENCE OF FUTURE TEACHERS (Psychology Travelogs, 2025)
The article analyzes current trends in the development of emotional and ethical competence of future teachers, which is defined as a holistic system of knowledge, skills and abilities that ensures the ability of an individual to be aware of and regulate their own emotional states, adequately perceive the emotions of others, effectively interact in interpersonal relationships, and make morally and ethically sound decisions in various professional and social situations. The scientific approaches to defining the content of the concept of “emotional-ethical competence of future teachers” are revealed, and the components of this concept – “emotional competence” and “ethical competence” are also characterized.It is specified that emotional competence is manifested in the ability to build harmonious interpersonal relationships, effectively respond to emotional influences and maintain emotional balance. It is determined that its components are emotional awareness, i.e. recognition of one's own emotions and their causes, emotional regulation as control over impulsive reactions, the ability to calm oneself in stressful situations, recognition of the emotions of others - empathy and sensitivity to non-verbal signals, emotional expression as an adequate transmission of one's emotions in communication.It is emphasized that a teacher's ethical competence is an integral quality of his personality, which provides not only knowledge of ethical norms and a professional code, but also the ability to apply them in specific pedagogical situations, especially in conditions of moral choice, conflicts, or emotionally charged interactions.It is emphasized that the development of emotional and ethical competence allows a teacher not only to understand ethical norms, but also to implement them through empathy, kindness, and tolerance.It is specified that the emotional and ethical competence of a future teacher includes: emotional skills as awareness and regulation of one's own emotions, recognition of the emotions of others, ethical awareness, which means the ability to evaluate one's own and others' actions from the standpoint of morality, social justice and pedagogical responsibility, moral and ethical action - behavior that takes into account the rights, feelings and interests of others, especially in the pedagogical environment.
Keywords: features; development; emotional and ethical competence; future teachers; factors